The Knowledge of Batak Toba Family in Feeding Toddler at Muliorejo Village, Sunggal District, Deli Serdang Regency - Kristina Mutiara Sihombing; Nurman Achmad (Talenta Publisher, 2021)
This study examines the knowledge of Batak Toba family in feeding toddlers in Muliorejo Village, Sunggal District, Deli Serdang Regency. The purpose of this study was to determine the knowledge of Batak Toba family in feeding toddler, how to serve toddler food, selecting toddler food and managing toddler food. The method used in this study is a holistic ethnographic method. The data collection technique used is through in-depth interviews, observation, and participation in the community, having knowledge related to research problems, and studying literature. The results of this study prove that the knowledge of Batak Toba family in feeding toddlers is very good, where parents who feed their children provide with a regular schedule in feeding, when the child is not at home or when the parents are at work, they keep fulfill the child's food by entrusting food to neighbors to give to his child, by also preparing provisions for the child.